The Effect of Innovation to Increase Growth Islamic Banking: Comparison of Islamic Banking Growth in Indonesia and Pakistan - Ade Pranajaya; Budi Dharma (Management Department Universitas Islam Negeri Sumatera Utara, 2022)
This article aims to see and compare the development of Islamic banking in Pakistan and Indonesia, with innovation indicators as the primary comparative justification. This study uses quantitative justification on available secondary data related to the growth of Islamic banking and qualitative justification that compares the impact of innovation on the development of these banking. The essential findings are that Islamic banking in Indonesia has very rapid growth compared to Pakistan, which incidentally has operated Islamic banking for a longer time. There are several reasons for these findings, including the population and distribution of Indonesia's territory, which is much larger than Pakistan. However, today's banking challenges are more widely accepted by Indonesian Islamic banking, where technological factors heavily influence growth. Therefore growth occurs by adapting innovations in banking organizations in Indonesia. Innovation is carried out by applying technology in banking business processes and strategic actions, such as the merger of Islamic banks to form the strength of Indonesia's most prominent Islamic bank.Keywords: Indonesian islamic banking, innovation, islamic banking, pakistan islamic banking